A macroeconometric policy model of the South African economy based on weak rational expectations with an application to monetary policy - Bauknecht, Klaus Dieter (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD) -- University of Stellenbosch, 2000.